Let be non-negative real numbers satisfying . Compute the minimum value of
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given expression can be factored as ( x + 3 y ) 2 + ( 3 y + 2 z ) 2 . As both of the squared terms are positive we know by the AM-GM inequality that the minimum will be achieved when x + 3 y = 3 y + 2 z ⟹ x = 2 z . In this case the given expression reduces to 2 ( 2 z + 3 y ) 2 .
Next, the given condition x y z = 3 2 becomes 2 y z 2 = 3 2 ⟹ 3 y = z 2 1 , in which case 2 ( 2 z + 3 y ) 2 = 2 ( 2 z + z 2 1 ) 2 .
Now by the AM-GM inequality 2 z + z 2 1 = z + z + z 2 1 ≥ 3 3 z × z × z 2 1 = 3 , where equality occurs when z = z 2 1 ⟹ z = 1 .
The desired minimum is then 2 ( 2 z + z 2 1 ) 2 = 2 × 3 2 = 1 8 , occurring when ( x , y , z ) = ( 2 , 3 1 , 1 ) .